South Africans commemorating in Poland: Making meaning through participation - Low, Carol (My University, 2008)
This research report focuses on the issues for participation in public memory projects, in the light of counter-monument critiques of audiences being ‘rendered passive’. Interviews with people who went on the 2005 March of the Living tour to Holocaust sites in Poland and then to Israel have been analysed in terms of themes and processes of meaningmaking. The written text of some of the material provided to them is also analysed. Meanings in the interviews notably occupied two discursive spaces that seem at odds with each other. The first was the discourse around what is a good way to memorialise – particularly when the memory is one of such enormity as the Holocaust. The second is the discourse around tolerance education – how do we ‘learn lessons’ from the Holocaust? The issues for heritage interpretation and tolerance education are explored.
Keywords: Holocaust memory; Public memory and participation; March of the Living; Tolerance education; Heritage interpretation; Memory and meaning making; South African Jews; Memorialisation; Jewish identity; Human rights education